The Effects of Social Information on Volunteering: A Field Experiment. (June 2018) - Moseley, Alice; James, Oliver; John, Peter; Richardson, Liz; Ryan, Matt; Stoker, Gerry
Research indicates that providing social information about other people's charitable donations can increase individual contributions. However, the effects of social information on volunteering time are underexplored. In this field experiment, we measure the effects of different levels of feedback about other people's time contributions (very high, high, and moderate) on individuals' hours of volunteering. The experiment was conducted with students from English universities volunteering for a variety of organizations and with a group of predominantly older people volunteering for a national charity in England. Social information did not increase volunteering for either group relative to a control group receiving individualized feedback with no social comparison. For students whose baseline volunteering time was lower than the median, social information had a demotivating effect, reducing their volunteering, suggesting that donating time is different to donating money.